BIM-Based Digital Fabrication Process for a Free-Form Building Project in South Korea - Joo-sung Lee; Nahyun Kwon; Nam-hyuk Ham; Jae-jun Kim; Yong-han Ahn (Advances in Civil Engineering)
Since the concept of building information modeling (BIM) was introduced in South Korea in 2008, digital fabrication concerning free-form shapes and complex parametric information has been expanding owing to the development of BIM software and tools. However, the digital fabrication process is inadequate in terms of efficiency and productivity because of the need to convert from conventional two-dimensional (2D) drawings to a BIM design; this adversely affects the unified design, fabrication, installation, and inspection processes. Moreover, an optimized process has not been developed thus far because the productivity of digital fabrication has not been quantitatively verified for various projects in the field. This study proposes a BIM-based digital fabrication process for prefabricated parts of buildings. In addition, a productivity analysis method based on the queuing model is proposed using personnel input and performance calculation data to verify productivity. It is expected that the digital fabrication process and productivity analysis model proposed here will be applied to complex digital fabrication works.